2019
DOI: 10.1016/j.neuroimage.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to heartbeats distinguish self from other during imagination

Abstract: Imagination is an internally-generated process, where one can make oneself or other people appear as protagonists of a scene. How does the brain tag the protagonist of an imagined scene as being oneself or someone else? Crucially, during imagination, neither external stimuli nor motor feedback are available to disentangle imagining oneself from imagining someone else. Here, we test the hypothesis that an internal mechanism based on the neural monitoring of heartbeats could distinguish between self and other. 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 56 publications
8
63
0
Order By: Relevance
“…A patient with insular lesions could perform well at interoceptive tasks provided that cardiac-related inputs mediated by the skin were available ( [175], but see also [176]). In addition, functionally relevant HERs were observed predominantly outside the insula in several experiments [111,128,130,131,135] ( Figure 5).…”
Section: Box 2 the Insula In Interoception And Beyondmentioning
confidence: 91%
See 2 more Smart Citations
“…A patient with insular lesions could perform well at interoceptive tasks provided that cardiac-related inputs mediated by the skin were available ( [175], but see also [176]). In addition, functionally relevant HERs were observed predominantly outside the insula in several experiments [111,128,130,131,135] ( Figure 5).…”
Section: Box 2 the Insula In Interoception And Beyondmentioning
confidence: 91%
“…(F) Confirmation of the findings in intracranial recordings in vmPFC, with a correlation between single-trial HERs and 'Me' ratings. Another study revealed that HERs distinguish between self and other [135]. (G-I) HERs predict visual perception at threshold [111].…”
Section: Temporal Contingencies Between External Stimuli and Heartbeatsmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant correlation between the global field alpha power and respiration was demonstrated in the eyes-closed resting state (Yuan et al, 2013). Other internal (visceral) movements, such as heartbeats, contribute not only to the DMN state, but also to encoding the self (Babo-Rebelo et al, 2016, 2019; Azzalini et al, 2019). The relative permanency of the self-referential and time to time modulation of mind wandering (Smallwood and Schooler, 2015; Kucyi, 2018) should be taken into account as a basic experimental control for the measurement of conscious events (Northoff et al, 2010).…”
Section: The Basic Control Of the Default Modementioning
confidence: 99%
“…As recommended by SPM12, we low-pass filtered the resulting HEP below 20Hz (again, with EEGLAB’s pop_neweegfilt). In deviation from our pre-registration, but following discussions with peer reviewers and investigation of similar decisions in previous studies of HEPs (Azzalini et al, 2019; Babo-Rebelo et al, 2016, 2019; Banellis & Cruse, 2020; Park et al, 2014; Petzschner et al, 2019), we chose not to apply any baseline correction to our data as cardiac activity is cyclical by nature and may therefore insert artefactual effects in post-R data. This decision also allows direct comparison with published results of Banellis and Cruse (2020).…”
Section: Methodsmentioning
confidence: 99%